Insights on common fungicides: A national survey on farmland soils from Mainland China - HOU, Jie; WANG, LiXi; WANG, JinZe; CHEN, LiYuan; HAN, BingJun; YANG, Tong; LIU, WenXin (Journal of hazardous materials, 2025)
Fungicides are a growing concern owing to their ecological and human health threats. In China, which is a large fungicide-consuming country, only a few provincial studies have reported several fungicide residues in agricultural soils. Additionally, terrestrial ecological risk assessments of pesticides are limited to the single species. This study showed that fungicides were commonly found in agricultural soils in mainland China, and the Σ13fungicides concentrations ranged from 0.0548 to 3183 μg/kg, with the major contributing component being difenoconazole. Spatial variation in fungicide concentrations was significant, with the highest concentrations observed in Southern China. The Σ13fungicides concentration was higher in soils covered with plastic films compared to uncovered soils, possibly because microplastics from agro-film sources promote fungicide retention in the soil. Among the crop types, the highest fungicide residues were found in soils planted with fruits. In addition, this study was the first to use the probabilistic species sensitivity distribution (pSSD) approach to deduce the predicted no-effect concentrations of major fungicides as terrestrial safety thresholds. Particularly, soil texture conditions may influence the hazard assessment of fungicides. Finally, from the species taxa perspective, the proportions of ecological risks of carbendazim and tebuconazole in agricultural soils in China were 4.3 % and 5.9 %, respectively. [Display omitted] •Fungicide residues are common in the agricultural topsoil of mainland China.•Significant spatial variation of fungicide residues affected by multiple factors.•Microplastics from agro-film sources might promote fungicide trapping in the soil.•Terrestrial safety thresholds of major fungicides were deduced using pSSD.•Soil texture affected fungicide toxicity assessment for the species taxa level.